EFFECT OF TEMPERATURE ON THE EXTRACTION OF BIOACTIVE COMPONENTS OF PALM KERNEL (ELAEIS GUINENSIS) OIL EXTRACTS - OLADIPE, TUNMISE; Owoleke, Veronica A.; Adegbegi, Ademuyiwa J.; Taiwo, Abayomi A.; Ibiyemi, David A.; Makinwa, Funmilayo O.; Oludare, Tayo T.; Arudi, Gloria A.; Ekeyi, Yusuf; Salawudeen, Shuaibu; Dada, Gloria (FUDMA Journal of Sciences, 2025)
Palm kernel (Elaeis guinensis) oil (PKO), which is derived from the seeds of the oil palm tree, has been traditionally used in various cultures for its potential health benefits.  This study investigated the effects of temperature (High >100°C and low
Keywords: Extraction Temperature; GC-MS profiling; FTIR analysis; Palm Kernel oil extracts